EFFECT OF VARIOUS LEVELS OF METABOLIZE ENERGY ON GROWTH PERFORMANCE OF CLARIAS JAENSIS FINGERLINGS (BOULENGER, 1909) - Gwladys, Tsoupou Kuété Suzy; Thomas, Efole Ewoukem; Ottoko, Moussala; Joseph, Tchoumboue (International Journal of Research -GRANTHAALAYAH, 2018)
The aim of this study was to contribute to the improvement of knowledge on the growth of endogenous catfish of Cameroon Clarias jaensis to develop the standards of his breeding. For this purpose, 396 fingerlings (36.7 ± 10.1 g) were divided into four comparable group with three replications. Four experimental rations containing 3000, 3100, 3200 and 3300 Kcal/kg of metabolize energy were distributed in these group at 5% of ichtyobiomasse. Except the feed intake and survival rate, other growth characteristics were comparable (P>0.05) between rations. The higher feed intake and the lowest consumption index were recorded with the ration containing 3000 Kcal/kg. The weight (95.10 ± 8.14 g), total length (23.77 ± 1.15 cm), weight gain (58.70 ± 9.49g), average daily gain (1.01 ± 0.16 g), specific growth rate (1.66 ± 0.26%) and K factor (0.71 ± 0.05) were higher with the ration containing the lowest level of energy. This reveals that Clarias jaensis fingerlings requires less energy for growth compared to other catfish like Clarias gariepinus. In view of the above and given the cost of manufacturing the food, the ration containing 3000 kcal/kg would be agro economically sustainable although the search for the optimal level of energy remains.